Distance-Based Topological Descriptors on Ternary Hypertree Networks. (28th September 2022) - Yu, Yun; Xavier, D. Antony; Varghese, Eddith Sarah; Mathew, Deepa; Siddiqui, Muhammad Kamran; Fufa, Samuel Asefa
Abstract : Topological indices are numeric parameters which portray the topology of a subatomic structure. In QSAR/QSPR analysis, topological descriptors play a vital role to examine the topology of a network. An interconnection network is a structure whose components are connected physically according to some pattern. In this paper, an interconnection network, ternary hypertree, which is a structural combination of complete ternary tree and hypertree, is introduced. We have evaluated the topological descriptors grounded on the distances for the ternary hypertree. The analytical expressions for Wiener, different types of Szeged, and Mostar indices are determined.